2009
DOI: 10.1074/jbc.m109.030411
|View full text |Cite
|
Sign up to set email alerts
|

Differential Effect of Membrane Cholesterol Removal on μ- and δ-Opioid Receptors

Abstract: According to the lipid raft theory, the plasma membrane contains small domains enriched in cholesterol and sphingolipid, which may serve as platforms to organize membrane proteins. -ol]enkephalin responses back to control values, and were confirmed in SH-SY5Y cells endogenously expressing -opioid receptors. The effects of M␤CD may be due to uncoupling of the receptor from G proteins but were not because of decreases in receptor number and were not mimicked by cytoskeleton disruption. In contrast to the results… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
21
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 63 publications
(24 citation statements)
references
References 61 publications
3
21
0
Order By: Relevance
“…We now report the distribution of AC isoform proteins in lipid and non-lipid rafts, using sucrose gradient fractionation samples from these cells. Among the AC isoforms only AC5/6 protein (using an antibody that recognizes both AC5 and AC6) was expressed mainly in lipid rafts in these kidney cells, in agreement with previous reports (13, 14, 16, 17, 23) (Figures 2A and 2B, upper panels ). In the basal state, more AC5/6 was distributed in lipid rafts than in non-lipid rafts and to a greater extent in HEK-hD 1 R cells (84.5±2.3 % of total density units, DU) than HEK-hD 5 R cells (69±3.1 % total DU) (P<0.05, n=4, ANOVA) (Figure 2A).…”
Section: Resultssupporting
confidence: 93%
See 3 more Smart Citations
“…We now report the distribution of AC isoform proteins in lipid and non-lipid rafts, using sucrose gradient fractionation samples from these cells. Among the AC isoforms only AC5/6 protein (using an antibody that recognizes both AC5 and AC6) was expressed mainly in lipid rafts in these kidney cells, in agreement with previous reports (13, 14, 16, 17, 23) (Figures 2A and 2B, upper panels ). In the basal state, more AC5/6 was distributed in lipid rafts than in non-lipid rafts and to a greater extent in HEK-hD 1 R cells (84.5±2.3 % of total density units, DU) than HEK-hD 5 R cells (69±3.1 % total DU) (P<0.05, n=4, ANOVA) (Figure 2A).…”
Section: Resultssupporting
confidence: 93%
“…AC3 protein was also present in lipid and non-lipid rafts in HEK-hD 1 R, in agreement with previous reports (13, 14, 23), and hRPT cells, but present only non-lipid rafts in HEK-hD 5 R cells, supporting the aforementioned notion that the concomitant expression of a specific receptor may alter AC localization in membrane microdomains. Fenoldopam decreased AC3 protein in lipid rafts in HEK-hD 1 R and hRPT cells but had no effect in HEK-hD 5 R cells (Figure 2C).…”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…Representative blots of three different experiments are shown. data (58). Despite the failure of regulating DOR localization, our studies revealed that chronic morphine treatment results in the recruitment of the entire pool of membrane raft located c-Src to non-raft membranes.…”
Section: Discussionmentioning
confidence: 78%